Consumer preference for specific beef attributes in Peninsular Malaysia - Jamil, Siti Hawa (2015)
Recent food industry trends have driven changes in the Malaysian food consumption. By increasing the consumer concerns over food safety, they are able to purchase food products not only to serve their basic needs but also for fulfill their various goods quality standards needed. In Malaysia beef has only recently gained popularity and given the changing nature of the availability of food and preferences, the Malaysian people are becoming more health conscious with their food choices and their beef preference has been tracking on a variety of attributes. Food safety, quality, health, price and the impact of the country of origin on beef choice h ave been widely examined and have revealed to be the relatively dominant attributes. The preference for beef has caused respondent to become more aware on how to get the best quality of beef for consumption. Thus respondents are searching for beef preferences that are safe to consume and close to their main choices. Nowadays Malaysians are experiencing dramatic changes in their lifestyles which impact the ways they purchase food. In line with the growing affluence and urbanization, Malaysian respondents are exposed to different types and parts of beef like the main cut known as chuck, rib, sirloin, short loin, round, flank, short rib and also leg in many food outlet s, fast food restaurants, supermarkets, night markets, and also farmers markets. Each respondent may have his or her own preference and it may vary depending on the form of preparation, texture, taste, color, freshness and also the country of origin. However, the market for preference for specific beef attributes in Malaysia is still at its infancy though people are giving it a very positive response. Beef preference refers to the attributes which make this type of food safe for consumption and provide a fine quality after it goes through a hygienic process during production.The objective of this study is to determine the preferences of the Malaysian consumers for specific beef attributes. A survey was conducted in Peninsular Malaysia where 1164 respondents were interviewed through a structured questionnaire to gather information on their preferences, attributes and attitudes towards beef preference. A Food Choice Model is applied in this study. Descriptive statistics, chi-square, factor analysis and hierarchy regression were used to analyze the collected data. The results indicate that there is a significant association between the consumers’ demographic profiles and their beef preference. Overall, the majorities of consumers consume beef regularity; prefer local fresh and tender beef which they usually purchase at traditional markets. Thus, the study indicates that there has been a relationship between consumers’ socio-demographic variables such as gender, age, education and income level and consumer preference for beef consumption in terms of preference for local beef, freshness, tenderness and also that which is purchased at a traditional market. Based on the factor analysis, seven factors have been identified that can influence the consumer preference for specific beef attributes. These factors are as follow: consumer sensory attributes, society influence, price, attitude, quality, country of origin, and safety concern. In addition, the results of the hierarchy regression model show that not only the attributes, price, country of origin and society play a role in determining beef choice and preferences among Malaysians, but attitude also influences the relationship between these factors and beef preference. Some of the factors have not shown any significant relationship with beef preference such as price and society. However by adding attitude as moderator, the relationship either improves or becomes significant. This shows the important role of attitude in moderating the relationship between the factors and product preference. Due to the increase in beef consumption in Malaysia, there is a need for relevant marketing strategies to be developed by the government or private organizations to increase in beef production. Based on these results it is suitable to segment the respondents according to their preferences and develop a different marketing strategy for each segment of the market. In this study the main concerns of consumers are attributes and country of origin therefore marketers are able to determine the core value of beef consumption for the consumers in order to develop future market strategies. Consumers also value local beef more, therefore, policy makers can take this into consideration by providing greater facilities for cattle farmers or developing and adopting better farm systems to improve beef industry in Malaysia.